(untitled) (Journal of Engineering, 2019)
This research presents a study for precipitating phosphorus (as phosphate ion) from simulated wastewater (5ppm initial concentration of phosphorus) using calcium hydroxide Ca(OH)2 solution. The removal of phosphorus by Ca (OH)2 solution is expected to be very effective since the chemical reaction is of acid-base type but Ca(OH)2 forms complex compound with phosphate ions called. Hydroxyapatite Ca5 (PO4)3OH. hydroxyapatite is slightly soluble in water. This research was directed towards sustainable elements as phosphorus. Kinetics of the dissolution reaction of hydroxyapatite was investigated to find the best factors to recover phosphorus. The effect of concentration of Ca(OH)2 (180- 380 ppm) on phosphorus precipitation on the outputs like the residual phosphorus concentration in the simulated solution, the percentage removal of phosphorus and the weight of the precipitate was also studied. The residual phosphorus decreased with increasing Ca(OH)2 concentration while the percentage removal, as well as the weight of the precipitate, increased with increasing Ca(OH)2 concentration at constant temperature and mixing speed. The best Ca(OH)2 concentration was obtained depending on the lowest amount of the residual phosphorus concentration. The best value obtained was 230 ppm at a fixed mixing speed of 400 rpm and a temperature of 20°C. The best value for Ca(OH)2 concentration under fixed stirring speed and temperature was applied on a real wastewater taken from the detergent factory. The percentage removal was 30. 69% due to the complexity of the real sample. Oxalic acid was chosen to dissolve hydroxyapatite because it is an organic acid, less hazardous than mineral acids and of less cost. Kinetics of the dissolution reaction of hydroxyapatite in (160 ppm) concentration oxalic acid under ambient conditions (20°C and 1 atm (and mild stirring (200 rpm) was studied using the differential method for determining the order of the reaction which was 0.4296 and the rate constant 0.0743 (L/mg)-0.5704. min-1. The reaction was considered as a rate-controlled reaction.